Fingerprinting ambient air to understand bioaerosol profiles in three different environments in the South East of England - Garcia Alcega, Sonia; Nasir, Zaheer A.; Cipullo, Sabrina; Ferguson, Robert M. W.; Yan, Cheng; Whitby, Corinne; Dumbrell, Alex J.; Drew, Gillian H.; Colbeck, Ian; Tyrrel, Sean F. (Elsevier, 2020)
Molecular and chemical fingerprints from 10 contrasting outdoor air environments, including three agricultural farms, three urban parks and four industrial sites were investigated to advance our understanding of bioaerosol distribution and emissions. Both phospholipid fatty acids (PLFA) and microbial volatile organic compounds (MVOC) profiles showed a different distribution in summer compared to winter. Further to this, a strong positive correlation was found between the total concentration of MVOCs and PLFAs (r = 0.670, p = 0.004 in winter and r = 0.767, p = 0.001 in summer) demonstrating that either chemical or molecular fingerprints of outdoor environments can provide good insights into the sources and distribution of bioaerosols. Environment specific variables and most representative MVOCs were identified and linked to microbial species emissions via a MVOC database and PLFAs taxonomical classification. While similar MVOCs and PLFAs were identified across all the environments suggesting common microbial communities, specific MVOCs were identified for each contrasting environment. Specifically, 3,4-dimethylpent-1-yn-3-ol, ethoxyethane and propanal were identified as key MVOCs for the industrial areas (and were correlated to fungi, Staphylococcus aureus (Gram positive bacteria) and Gram negative bacteria, R = 0.863, R = 0.618 and R = 0.676, respectively) while phthalic acid, propene and isobutane were key for urban environments (correlated to Gram negative bacteria, fungi and bacteria, R = 0.874, R = 0.962 and R = 0.969 respectively); and ethanol, 2-methyl-2-propanol, 2-methyl-1-pentene, butane, isoprene and methyl acetate were key for farms (correlated to fungi, Gram positive bacteria and bacteria, R = 0.690 and 0.783, R = 0.706 and R = 0.790, 0.761 and 0.768). The combination of MVOCs and PLFAs markers can assist in rapid microbial fingerprinting of distinct environmental influences on ambient air quality.